BIOACTIVITY, SYNTHESIS, AND INNOVATIVE APPLICATIONS OF TANNINS: A LITERATURE REVIEW - Thoriq, Thoriq; Pramesthi, Ayudya Restu Yudha (VARIABLE RESEARCH JOURNAL, 2024)
Tannin is a water-soluble phenolic secondary metabolite compound with the ability to precipitate gelatin, alkaloids and proteins. Tannins have a very high abundance in nature. Tannins can be found in the seeds, skin, stems and roots of various types of plants such as tea, chocolate, coffee and grapes. Hydrolyzed and condensed tannins are two types of complex polyphenolic compounds that are attracting attention in bioactivity research and industrial applications. This article provides a comprehensive literature review on the bioactivity, synthesis, and utilization of these two types of tannins. Some of the bioactivities of tannins include antioxidant, antimicrobial, antitumor and anti-inflammatory, all of which provide potential for further development. With these various bioactivities, tannins have been widely studied in terms of their structure, synthesis and biosynthesis. Apart from that, tannin compounds have also been widely used in the pharmaceutical, textile and adhesive industries. Tannin compounds provide promising potential as multifunctional natural ingredients with wide applications. However, more research is needed to understand its full potential and utilization efficiency.